Cost-effectiveness of transcatheter edge-to-edge repair in secondary mitral regurgitation. Issue 9 (25th January 2022) - Cohen, David J; Wang, Kaijun; Magnuson, Elizabeth; Smith, Robert; Petrie, Mark C; Buch, Mamta Heena; Abraham, William; Lindenfeld, Joann; Mack, Michael J; Stone, Gregg W; Cleland, John G F
Abstract : Background: Transcatheter edge-to-edge mitral valve repair (TMVr) improves symptoms and survival for patients with heart failure with reduced left ventricular ejection fraction (HFrEF) and severe secondary mitral regurgitation despite guideline-recommended medical therapy (GRMT). Whether TMVr is cost-effective from a UK National Health Service (NHS) perspective is unknown. Methods: We used patient-level data from the Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with Functional Mitral Regurgitation (COAPT) trial to perform a cost-effectiveness analysis of TMVr +GRMT versus GRMT alone from an NHS perspective. Costs for the TMVr procedure were based on standard English tariffs and device costs. Subsequent costs were estimated based on data acquired during the trial. Health utilities were estimated using the Short-Form 6-Dimension Health Survey. Results: Costs for the index procedural hospitalisation were £18 781, of which £16 218 were for the TMVr device. Over 2-year follow-up, TMVr reduced subsequent costs compared with GRMT (£10 944 vs £14 932, p=0.006), driven mainly by reductions in heart failure hospitalisations; nonetheless, total 2-year costs remained higher with TMVr (£29 165 vs £14 932, p<0.001). When survival, health utilities and costs were projected over a lifetime, TMVr was projected to increase life expectancy by 1.57 years and quality-adjusted life expectancy by 1.12 quality-adjusted life-years (QALYs) at an incremental cost of £21 980, resulting in an incremental cost-effectiveness ratio (ICER) of £23 270 per QALY gained (after discounting). If the benefits of TMVr observed in the first 2 years were maintained without attenuation, the ICER improved to £12 494 per QALY. Conclusions: For patients with HFrEF and severe secondary mitral regurgitation similar to those enrolled in COAPT, TMVr increases life expectancy and quality-adjusted life expectancy compared with GRMT at an ICER that represents good value from an NHS perspective.